The effects of apathy and depression on cognitive and functional outcomes in Alzheimer's disease - Lekhutlile, Tlholego (Department of Psychology, 2021)
Alzheimer's disease (AD) is the most common cause of dementia initially characterised by short-term memory deficits followed by a progressive cross domain cognitive and functional decline over time and loss of independence in carrying out activities of daily living (ADL). Apathy and depression are also the two most frequent neuropsychiatric sequalae associated with AD and have an impact on patients' ability to execute ADLs. Little is still known if apathy subdomains differently predict ADL performance in these patients. In this study, we aimed to quantitatively investigate if global apathy and depression predict ADL performance. We also wanted to establish if the apathy evaluation scale (AES) items resolve into three factors as proposed by Marin and if those factors differently predict performance of ADLs. We recruited a sample of 115 patients diagnosed with probable or possible AD. Basing on current literature, we hypothesised that apathy and depression predict ADL performance. We also hypothesised that AES items will load into three factors relating to cognitive, behavioural and affective apathy subdomains and that these subdomains will differentially predict ADL performance in our patient sample. Our results indicated that high apathy and depression symptoms were associated with problems to carryout ADLs. They also indicated that AES items resolved into a three factor solution in analogy with Marin's conceptualisation but they did not cluster in the manner that he proposed. Finally, when these factors are regressed simultaneously, (derived from factor analysis) only behavioural apathy significantly predicted ADLs.